Biblioteka Opactwa św. Wojciecha Mniszek Benedyktynek w Staniątkach - Dudziak-Kowalska, Małgorzata; Janczak, Barbara (Archiwa, Biblioteki i Muzea Kościelne, 2015)
The article is devoted to the history and present state of the library of The Abbey of Benedictine Nuns in Staniątki, one of the oldest monasteries in Poland. Development of the library throughout centuries has been outlined an the contents of the book collection have been described. Special attention has been paid to the musical collections originating from XVI-XVIII cc., which currenty can be accessed by the digital library. The study is an attempt to present the isssue from a librarian’s point of view. The problems discussed in the article refl ect diffi culties and challenges that have to be faced by numerous Polish monastery libraries.